The difficulties faced by students in producing free-writing: A study at STKIP Bina Bangsa Getsempena - Rahmi Fhonna (Universitas Syiah Kuala, 2014)
Writing is a means of communication to convey meaning as well as a medium for self-expression and self assessment and also for teacher-assessment. In the tertiary context, writing even has more complex meanings because of its social context and epistemological issues of knowledge. This study was conducted to identify errors and mistakes made in free-writing by students at STKIP Bina Bangsa Getsempena and to investigate the reasons they faced numerous difficulties in producing good free-writing as well as to investigate the students’ opinions towards the activity of writing in general and also the comments of their lecturers on their free-writing assignments. 18 free-writing assignments were collected from 18 students as samples for this study. A questionnaire was also distributed to strengthen the data obtained from the writings. The written assignments were then analyzed by using the form feedback framework, in terms of conventional grammatical errors, adapted from Ashwell (2000). The findings showed 6 categories of grammar that were often misused in the students’ free-writing, namely agreement/verb-tense, spelling, articles/determiners/plurals, lexical choice, pronoun and preposition/collocation. The results from the questionnaires revealed that the main obstacles faced by the students in producing free-writing were their lack of ideas/difficulties in organizing ideas as well as their problems with grammar.